2021
DOI: 10.3390/foods10112771
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Thermophoresis Reveals Oxidized Glutathione as High-Affinity Ligand of Mal d 1

Abstract: Pathogenesis-related (PR)-10 proteins, due to their particular secondary structure, can bind various ligands which could be important for their biological function. Accordingly, the PR-10 protein Mal d 1, the major apple allergen, probably also binds molecules in the hydrophobic cavity of its secondary structure, but it has not yet been investigated in this respect. In this study, various natural products found in apples such as flavonoids, glutathione (GSH), and glutathione disulfide (GSSG) were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…They determined significantly lower K D values for binding of (+)-CAT than (−)-EC with Mal d 1.02 and also reported different K D values for (+)-EC and (−)-EC, further illustrating the impact of stereo centers on the binding affinity. By docking studies, they identified hydrogen bonds and hydrophobic interactions as the main factors for Mal d 1.02–flavonoid interactions . However, it remains unknown if those generally lower K D values in the μM range are due to the analytical approach or due to the characteristics of the specific isoallergen (Mal d 1.02).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They determined significantly lower K D values for binding of (+)-CAT than (−)-EC with Mal d 1.02 and also reported different K D values for (+)-EC and (−)-EC, further illustrating the impact of stereo centers on the binding affinity. By docking studies, they identified hydrogen bonds and hydrophobic interactions as the main factors for Mal d 1.02–flavonoid interactions . However, it remains unknown if those generally lower K D values in the μM range are due to the analytical approach or due to the characteristics of the specific isoallergen (Mal d 1.02).…”
Section: Discussioncontrasting
confidence: 99%
“…Chebib et al studied interactions between Mal d 1.02 and PP by applying Microscale Thermophoresis . They determined significantly lower K D values for binding of (+)-CAT than (−)-EC with Mal d 1.02 and also reported different K D values for (+)-EC and (−)-EC, further illustrating the impact of stereo centers on the binding affinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first step, we probed the reactivity of Mal d 1 toward L-ascorbate using solution NMR spectroscopy. The addition of L-ascorbate to samples of Mal d 1 did not have an immediate impact on the backbone amide 1 H 15 N-HSQC spectrum of this protein (Figure S2), even at 15-fold excess, indicating that, unlike other amphiphilic compounds of similar size [24], L-ascorbate does not bind to the internal cavity of this protein. However, incubation with L-ascorbate for several days initiated a slow but defined change of the backbone amide 1 H 15 N-HSQC spectrum (Figure 1B).…”
Section: Identification and Characterization Of Mal D 1 Ascorbylationmentioning
confidence: 94%
“…In this context, the ability of various natural products found in apples such as flavonoids, glutathione, and glutathione disulfide to bind the major allergen of this fruit Mal d 1 have been studied using microscale thermophoresis by Chebib and Schwab [ 5 ]. Authors found that while flavonoids are bound to Mal d 1 via hydrophobic and polar interactions, glutathione binding to this allergen occurs by hydrophilic hydrogen bonds and van der Waal forces, suggesting differential modification of the allergenicity of Mal d 1 [ 5 ]. Processing food products can induce modifications in the proteins not only by modifying their allergenicity but also by changing their digestibility.…”
mentioning
confidence: 99%